A Location - Allocation Model For Pedestrian Footbridge infrastructure: A Case Study on the South Africa's National Roads Agency Limited (SANRAL) Network in Gauteng - Mabe, Malesiba Millicent (Department of Civil Engineering, 2021)
Road fatalities are one of the leading causes of unnatural deaths in developing countries, such as South Africa. According to the Road Traffic Management Corporation (2017), the number of road traffic fatalities were recorded to be 11 676 in the year 2016 and 42.6% of these road traffic fatalities involved pedestrian. According to the National Road Safety Strategy 2016 – 2030 most pedestrian crashes are due to illegal pedestrian crossings mainly across high speed roads (highways) (Department of Transport, 2011). The research study aims to develop a geo-spatial model to determine the most suitable location to allocate pedestrian footbridge infrastructure along the South African National Road Agency Limited (SANRAL) network in Gauteng Province. Previously road planning and design in South Africa followed international best practices, with development of the highway road system mainly orientated to serve motorised transport by primarily providing infrastructure for vehicular traffic along the highways , as pedestrians and highways were not expected to coexist in any proximity to each other. The presence of pedestrians along highways can no longer be ignored and there is a great need to overcome the highly fragmented spatial planning formed by the apartheid policies. For most non-motorised transport (NMT) users in South Africa, highways offer the shortest and most efficient direct routes, but also represent a major obstacle for many pedestrians who are separated by them. Limited studies on the location and allocation of the pedestrian footbridge for pedestrians are reported in the literature, further research in this field should be considered, especially along the SANRAL network where there are high number of residential areas along high-speed roads, this behaviour is unique and common in South Africa. Based on a literature review the factors affecting the location and allocation of pedestrian footbridges were identified, the following were factors identified: population density (serviced by the pedestrian footbridge), land use activities, socio-economic characteristics of the population (e.g. Gender, employment, race, and income level), crash hotspots/statistics (along the route), distance to access bridge and vehicle traffic volume along the route. From these factors spatial data was gathered to carry out spatial multi-criteria analyses (SMCA). The results from the spatial analysis showed that high population densities adjacent to highway, accessibility and land use are key in the location of pedestrian footbridge. The results also show that there is a strong correlation between: land use diversity, socio-economic, crash hotspots/statistics (along the route), vehicle traffic volume and population density (serviced by the pedestrian footbridge). The higher an area has these factors, the Higher the Pedestrian Footbridge location index (high pedestrian footbridge location demand), hence the recommendation to allocate in those locations.